Fluoride Concentration in Tap Water from Different Regions in Thailand: Konsentrasi Fluoride dalam Air Keran dari Berbagai Daerah di Thailand - Putraphan, Boonsong; Nantanapiboon, Dusit; Osathanon, Thanaphum (Dentika: Dental Journal, 2022)
Fluoride supplementation in drinking tap water is one of the well-known effective methods for dental caries prevention. However, overexposure to fluoride following excessive fluoride intake from drinking water leads to dental fluorosis. Therefore, the assessment of daily fluoride consumption is required to calculate the optimal fluoride intake. The present study investigated the fluoride concentration in tap water collected from different areas in Thailand. A total of 27 locations were selected. Three samples of tap water (500 mL each) were independently collected from one location. Each sample in the same location was collected from the same faucet of tap water and stored in different containers. The samples were collected by dental students or dentists who worked in the selected areas from March 2020 to June 2020. Briefly, the faucet was cleaned with the tap water and the water was run from the faucet for 1-2 mins. Then, water was collected in 500 mL bottles and immediately capped. Samples were then stored at room temperature in tightly sealed bottles until analysis. Findings showed that most samples contained fluoride at a concentration lower than 0.7 mg/mL. Further, the water pH was in the range of 6.81-8.37. These levels were lower than the cut-offs established by the World Health Organization (WHO) for maximum levels of fluoride and pH in drinking water. In conclusion, the present study demonstrated that fluoride levels in tap water from different regions in Thailand are lower than those recommended by WHO for fluoride levels in drinking water.